Efforts to Improve Student Learning Outcomes Using Curriculum Based LKPD Independence in Language Learning Indonesia is in the High Class VI Mutiara Street Science Primary School Kuala Langkat - Hizzatul Arfiah, Siti; Adnurul Lubis, Uyuun; Mutia Sari, Sindi (Berpusi Publishing, 2023)
This research aims to improve student learning outcomes by using independent curriculum- based LKPD in Indonesian language learning in the sixth grade of SD IT Mutiara Ilmu Jalan Kuala Langkat. The approach used is a quantitative approach by distributing LKPD to class VI students at SD IT Pearl Ilmu. This research was carried out in two stages of meetings, at each meeting the data collection system involved distributing LKDP to explore memories of the Indonesian language lessons that had been studied. Each meeting uses research procedures, which consist of planning, implementation, observation and reflection stages. The subjects of this research were class VI students at SD IT Pearl Ilmu, which had a total of 30 students. The instruments used in this research are field note tests, subjectivity, observation and documentation. The data used is descriptive analysis and looks at student learning outcomes using LKPD in class VI SD IT Pearl of Kuala Langkat road science. At the first meeting the completeness score was 100% or 30 students attended, out of 30 students 21 students or 70% got good indicators and at the meeting secondly, there was a classic significant increase, there were 22 students or a percentage of 73.33% who got very good indicators. So it can be concluded that using independent curriculum-based student worksheets (LKPD) in Indonesian language learning can improve student learning outcomes in class VI Sd IT Mutiara Ilmu Jalan Kuala Langkat.